Linking forest policy issues and decision support tools to promote the development of integrated policy analysis in Europe - Linkevičius, E.; Nordström, E. M.; Garcia-Gonzalo, J. (Natural Resources Institute Finland, Luke, 2016)
This study aims to improve understanding and capacities in the use of forestry DS tools for integrated policy analysis. The methodological framework and the questionnaire of this study were developed within the frames of COST Action FP1207, “Orchestrating forest-related policy analysis in Europe (ORCHESTRA)”. The main conclusion is that there are DS tools suitable to support forest policy areas. Yet, the spread and usage of DS tools in forest policy is limited for several reasons.
Keywords: forest policy area; forest decision support systems; expert interviews